Learner-Centred Discourse in an English Language and Literature Classroom in Pakistan (PJDOL, 2023)
The paper investigated the differences between teacher-centered (TC) and leaner-centered (LC) methods and the views of the students about the same in an academic context in Pakistan. Keeping in view the nature of research, mainly a qualitative research method was used. Data was collected by audio-recording two classroom discourses on LC and TC modes respectively. Further a questionnaire with a focus on open-ended questions was also served to the participants of the study. Data was analyzed informed by Conversation Analysis and Critical Discourse Analysis (CDA). The study showed certain conversational and ideological differences between the two types of discourses: TC and LC.